Postsurgical cutaneous defect treated with PRP: A case report - Verzoviti, Ioanna; Nathanailidou, Maria; Prodromou, Christina Maria; Koulouri, Maria Eleni; Keramidaris, Dimitrios (Acta Biomedica Atenei Parmensis, 2024)
There are visible cosmetic flaws that are difficult to treat after large open abdominal surgeries. The centrifugation of whole blood yields autologous platelet-rich plasma (PRP), which contains numerous growth factors that encourage vascular development and wound healing. The favorable outcomes in skin rejuvenation and clinical application of PRP suggest that it is effective for wound healing. We may have a hard time posing a big challenge because of the patient's clinical state, the absence of usable tissue and any comorbidities the patient may have. Herein we report the case of a 73-year-old patient, who was presented with a postsurgical abdominal tissue defect that could not be healed differently. There are few reports on the use of PRP for cutaneous defects, thus our scope is to highlight the usefulness and effectivness of this non-invasive method for the wound healing of any large skin defects.